Pengembangan Video Animasi Toontastic Terintegrasi Model Kooperatif STAD pada Pembelajaran PPKn di Madrasah Ibtidaiyah - Maisyaroh Maisyaroh; Novita Hanum; Mukti Kanaya Sidiq (MAN 4 Kota Pekanbaru, 2026)
This study aims to develop and assess the feasibility of animated video learning media using Toontastic application, integrated with the Student Teams Achievement Divisions (STAD) cooperative learning model. The development focused on Civics Education (PPKn), specifically on the topic of individual characteristic diversity for fourth-grade students at MIS Darul Hikmah, Medan. This study employed a Research and Development (R&D) approach utilizing the 4D model (Define, Design, Develop, and Disseminate). Product feasibility was evaluated through expert validation and limited field trials. The results indicated that the developed media was categorized as